TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP BAGI HASIL PRODUK SIMPANAN MUDHARABAH BERJANGKA : STUDI KASUS PADA BMT MASLAHAH LILUMMAH CABANG SUKOWONOS KABUPATEN JEMBER - Bachrul Ulum; Roki Ardinsyah Saputra; Mohammad Rusdi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research aims to find out about how the implementation of profit sharing mudharabah futures savings products at BMT Maslahah Lilummah Sukowono Branch and find out how Islamic law views the implementation of profit sharing mudharabah futures savings at BMT Maslahah Lilummah Sukowono Branch this research uses descriptive qualitative methods where this research is carried out at BMT Maslahah Lilummah Sukowono Branch. Data collection techniques in the form of interviews, observations and interviews the results of the study indicate that the implementation of product profit sharing at BMT Maslahah Lil Ummah Sukowono branch the contract carried out uses a mudharabah muthlaqah contract and the rules are in accordance with the rules of sharia economic law. with the rules of sharia economic law.